ONLINE SURVEY MANAGEMENT SYSTEM - Singh, Tejpal; Kumar, Avinash; Vihar, Kumari Bhawna; Singh, Aparna (IJRDO - Journal of Business Management, 2016)
Online survey offers cheapest data collection and processing cost, efficient service, easy data processing and wide coverage over traditional paper-and-pencil surveys; due to this its adoption recently has been inevitable. However, despite the number of advantages an online questionnaire can offer, there are still a number of problems and challenges related to authentication that need to be closely addressed. Multiple submissions, respondent authenticity/validity, and respondent’s anonymity are among the issues that hinder the proliferation of online surveys.